The relationship between unemployment and wellbeing: an updated meta-analysis of longitudinal evidence - Cigdem Gedikli (European Journal of Work and Organizational Psychology, 2023)
We provide an up-to-date quantitative synthesis of the evidence on the effect of unemployment on wellbeing based on 46 samples reported in 29 studies published between 1990 and 2020. Our sample includes longitudinal studies focusing on developed economies (e. g., EU-15 countries, UK, US, and Australia). We advance existing knowledge by exploring a wider range of wellbeing measures (both mental health and subjective wellbeing) and an extensive set of moderators capturing individual characteristics and country-level factors. In addition to the well-established negative impact upon mental health, our results present a negative relationship between unemployment and life satisfaction. In line with previous work, this negative association is stronger for men than women, and the longer the duration of unemployment, the larger the impact. We contribute to the existing evidence by pointing to the significant role in this relationship of gender, social and economic context, and norms/societal expectations regarding work. Finally, by utilizing longitudinal data and meta-analytic cross-lagged structural equation modelling, we present preliminary evidence on the existence of a reciprocal relationship between unemployment and wellbeing over time. While unemployment reduces wellbeing, poor wellbeing also leads to unemployment, indicating that individuals can become trapped in a cycle of unemployment and poor wellbeing.